Productivity Prediction and Simulation Verification of Fishbone Multilateral Wells - Wen Jing; Liu Xiao; Hu Haixia; Luo Wei (Geofluids)
As fishbone multilateral wells are increasingly used in the development of oil and gas fields, the need for the optimal design of multilateral well parameters has become increasingly urgent. Although the establishment of multilateral well productivity models has taken a step forward due to recently contributed research results, there are still few studies on model verification; that is, these models lack verification, and their reliability is uncertain, which increases the difficulty of their promotion and application in practice. Therefore, based on a more comprehensive horizontal well productivity prediction model, a fishbone multilateral well productivity prediction model was established in this work. Taking an oil field in the Middle East as an example, multilateral well productivity prediction and parameters sensitivity analysis were carried out, and the results were compared with the simulation results determined by using CMG digital simulation software. The established model was verified in terms of branch length, branch angle, and branch output contribution. The conclusions reached by these two methods were consistent, which verified that the established model was reliable.